The Aid Trade : International Assistance as Pathways for the Introduction of Invasive Alien Species - Murphy, Sean T.; Cheesman, Oliver D. (World Bank, Washington, DC, 2014)
It is now recognized that invasive alien species (IAS) pose a major threat to agricultural and natural ecosystems, and to human health and livelihoods. These non-native species, which are accidentally or intentionally introduced into new areas, range from microbes to mammals. This report examines the precise origins of many existing IAS problems, particularly in the developing world, which remain poorly understood. This complicates assessments of the relative importance of different vectors and pathways for IAS introductions, and the prediction of future risks. International assistance programs can facilitate both deliberate, and unintentional IAS introductions. Such misjudgments and accidents are costly; indeed, their negative effects may be far greater, and more long-lasting than the positive impacts of the aid programs from which they arose. It is thus suggested that knowing how, and from where, IAS are being introduced are important first steps in the development of effective prevention and early detection schemes. An urgent, and fuller, assessment is needed on the nature and severity of IAS threats associated with international assistance programs. Particular attention needs to be paid to vectors and pathways of movement. Part of the focus should be on case studies, in order to elucidate more fully constraints in relation to existing prevention schemes. Nonetheless, some actions should be considered in advance, including awareness raising to aid agencies, and promoting the development of voluntary codes of conduct, and risk assessments.